The Risk of Failure Assessment in Bina Marga Standard Designed Prestressed Concrete Girder Bridges under B-WIM Load Measurement - Widi Nugraha; Indra Djati Sidi; Made Suarjana; Ediansjah Zulkifli (Journal of Engineering and Technological Sciences, 2023)
The use of precast prestressed concrete girder bridges in Indonesia has been increasing rapidly due to their high quality, reliability, and faster construction on site. The girder components are typically designed for a specific bridge span and can be prefabricated. The Directorate General of Highways of the Ministry of PUPR (Bina Marga) has released a standard design for prestressed concrete girder bridges with a typical span of up to 40 m. This design is based on the bridge loading standard SNI 1725 2016, which determines the live traffic load through consensus due to limited data on actual traffic load measurement results. However, the Ministry of PUPR has been implementing actual traffic load measurements using weigh-in-motion (WIM) technology to directly measure the load of passing vehicles. In this study, a risk assessment of the failure risk of a standard Bina Marga bridge with a 40-m span prestressed concrete girder type was conducted based on B-WIM load measurements. The results of this assessment indicate that the standard Bina Marga bridge has a failure risk of 1.48 x 10-4, which is smaller than the acceptable risk of failure according to the AASHTO LRFD Bridge Design Specification as referenced in SNI 1725 2016.